2023
DOI: 10.3390/su151612313
|View full text |Cite
|
Sign up to set email alerts
|

Generation Mean Analysis, Heterosis, and Genetic Diversity in Five Egyptian Faba Beans and Their Hybrids

Mohamed S. Abd El-Aty,
Mahmoud A. El-Hity,
Tharwat M. Abo Sen
et al.

Abstract: The faba bean (Vicia faba L.) is a major legume crop; thus, it is important to apply various biometrical techniques to develop the most efficient breeding procedures to face biotic and abiotic stressors. During the four consecutive winter seasons of 2017–2021, five populations of five faba bean hybrids were studied at Sakha agricultural research station in Egypt. Five basic generations, including two parents (P1 and P2) and the first, second, and third generations, were studied. This analysis found significant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(6 citation statements)
references
References 53 publications
0
0
0
Order By: Relevance
“…Moreover, high heritability in a narrow sense, indicates that the genetic variance of additives played a vital role in the existence of variability. These results are similar to those reported previously [22,26,44,46]. Johnson et al [50] reported that to predict selection results for the best individuals, we need to estimate the heritability value with genetic advances, which are more valuable than the value of heritability alone.…”
Section: Discussionsupporting
confidence: 89%
See 3 more Smart Citations
“…Moreover, high heritability in a narrow sense, indicates that the genetic variance of additives played a vital role in the existence of variability. These results are similar to those reported previously [22,26,44,46]. Johnson et al [50] reported that to predict selection results for the best individuals, we need to estimate the heritability value with genetic advances, which are more valuable than the value of heritability alone.…”
Section: Discussionsupporting
confidence: 89%
“…In the case of crossing between inbreed lines, their progeny may achieve higher performance than them (hybrid vigor), as reported by Falconer [45]. The reduction in the mean performance of F 2 indicates an increment in inbreeding depression and vice versa, which implies the low genetic diversity of the parents [22,26,46]. In the potence ratio, values of measured characteristics, more than unity, reflect over-dominance effects.…”
Section: Discussionmentioning
confidence: 87%
See 2 more Smart Citations
“…The Middle East is frequently cited as the region of origin, although alternative research [ 2 , 3 ] points to Central Asia. Egypt uses faba beans extensively since they are an affordable food with good nutritional value, especially when it comes to their high protein content [ 4 ]. The average total protein content of faba beans is 29%, and they have a high production potential.…”
Section: Introductionmentioning
confidence: 99%